Editorial Hepatology Practice in Pakistan: Physician’s Perspective - Ayub Khan, Jibran Umar (International Journal of Pathology, 2023)
The hepatology patients in Pakistan are diversified like any other country presenting in various forms and manifestations. There is no dearth of chronic liver disease, non alcoholic fatty liver disease, acute and chronic hepatitis and even hepatocellular cancers. 1There has been rapid advancement in hepatology practice throughout the world with introduction of novel treatments but the complexity of patients is real challenge for experienced physicians and hepatologists. The interpretation of liver function tests and assessment of the patients is a real dilemma in its own self . Sometimes even an invasive investigation like liver biopsy can’t give you right answers. 2 While alcohol remains the most important cause of liver cirrhosis in the west, chronic hepatitis B and C are the most common culprits here. 3About few years ago most of emphasis was on screening the patients for both of them and then treating with interferon and ribavarin regimens for months .The novel therapies sofosbuvir and velpetsavir and the presence of very effective treatment choices have made the life of the physician very easy.Its convenient for the patients as well there is natural phobia towards injections affecting their compliance to a colossal extent .Even the hepatitis C treatment in special population like chronic kidney disease requiring hemodialysis , decompensated cirrhotics, liver transplant candidates and hepatocellular cancer patient has been revolutionized. We are following the updated guidelines of European Association for Study of Liver Diseases (EASL) when it comes to our practice though there are differences of opinions and clinical judgments.4